Emerging Innovations and Professional Skills Needed Within Pharmacy Curricula. (July 2020) - Olsen, Amanda A; Minshew, Lana M; Morbitzer, Kathryn A; Brock, Tina P; McLaughlin, Jacqueline E
To ensure students are prepared for the rapidly evolving world of health care, curricula must be aligned with emerging innovations, as well as professional skills likely to influence students' abilities to be successful. At the 2019 annual meeting of PharmAlliance institutions, we asked experts to identify innovations and professional skills necessary for the future of pharmacy practice. Experts identified a wide range of topics, including personalized and precision medicine, digital health, interprofessional collaboration, clinical decision making, and overcoming complexity and ambiguity. While these findings are useful for informing curriculum content, we must also commit to ensuring our pharmacy curricula are emerging, forward thinking, and effective at preparing students for the challenges in health care.